1983
DOI: 10.1104/pp.71.3.574
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Photosynthesis and Respiration

Abstract: The rate of dark CO2 efflux from mature wheat (Triium aestivum cv Gabo) leaves at the end of the night is less than that found after a period of photosynthesis. After photosynthesis, the dark CO2 efflux shows complex dependence on time and temperature. For about 30 minutes after darkening, CO2 efflux includes a large component which can be abolished by transferring Muminated leaves to 3% 0 and 330 microbar CO2 before darkening. After 30 minutes of darkness, a relatively steady rate of CO2 efflux was obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
101
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(120 citation statements)
references
References 23 publications
15
101
0
Order By: Relevance
“…An analogous effect, observed in wild-type plants of some other species (3), has been interpreted as evidence that the amount of respiration is responsive to the amount or form of storage carbohydrate (3). Because the starchless mutant accumulates high levels of soluble carbohydrate in the light which rapidly decline in the dark, it seems likely that, as suggested (2,3,6), the amount of respiration is proportional to the availability of substrate rather than to the demand for ATP and NADH. It remains to be seen if the abnormally high respiration of the mutant is due to alternative oxidase activity which has been invoked to explain substrate-regulation of respiration (3,15,29).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…An analogous effect, observed in wild-type plants of some other species (3), has been interpreted as evidence that the amount of respiration is responsive to the amount or form of storage carbohydrate (3). Because the starchless mutant accumulates high levels of soluble carbohydrate in the light which rapidly decline in the dark, it seems likely that, as suggested (2,3,6), the amount of respiration is proportional to the availability of substrate rather than to the demand for ATP and NADH. It remains to be seen if the abnormally high respiration of the mutant is due to alternative oxidase activity which has been invoked to explain substrate-regulation of respiration (3,15,29).…”
Section: Discussionmentioning
confidence: 97%
“…The effect of carbohydrate accumulation on the rate of dark respiration has received less attention but appears to have been consistently observed by a variety of approaches (2,6,29). The essential observation is that the rate of respiration is proportional to carbohydrate content or is stimulated by provision of exogenous carbohydrate.…”
mentioning
confidence: 99%
“…The fact that these plants were grown at high CO2 undoubtedly facilitated carbon accumulation and, perhaps, exaggerated possible genotypic differences in this character. The rate of respiration ofleaves in the dark may depend on the carbohydrate content, as shown in several species (2,5,6,8,16), and this dependence may have varied in the selected tobacco lines. The leaf respiration of selected SP lines was apparently less sensitive to carbon content, allowing a greater carbon accumulation per unit area and, perhaps, more efficient carbon storage for subsequent use in growth.…”
Section: Leaf Respiration In the Darkmentioning
confidence: 99%
“…Respiratory activity is often correlated with carbohydrate levels (Penning de Wries, Witlage & Kremer 1979;Azcón-Bieto & Osmond 1983;Farrar 1985;Amthor 1994;Felitti & Gonzalez 1998). It has been suggested that at high carbohydrate levels there could be more alternative pathway activity if excess substrate saturates the cytochrome pathway Lambers 1997).…”
Section: Metabolic Regulation Of Respiration 211mentioning
confidence: 99%